Protein deficiency decreases stereotypic behavior frequency and prevalence and activity in the striped mouse Rhabdomys dilectus chakae. Issue 2 (20th November 2017) - Pillay, Neville; Rimbach, Rebecca
Abstract: Diverse motivational triggers, including diet, elicit stereotypic behavior. We investigated whether diets comprised of different protein levels but similar levels of energy were associated with the occurrence of locomotor stereotypies in the striped mouse Rhabdomys dilectus chakae . In a first experiment, 20 stereotypic and 20 non‐stereotypic (10 subjects per sex and per group) juvenile (40 days old) subjects were placed on baseline (BP), high (HP) or low protein (LP) diet treatments (120 subjects in total). All subjects initially identified as stereotypic displayed stereotypic behavior in the BP and HP treatments on Days 60–63 and Days 80–83 compared to 35% and 12.5% of LP subjects, respectively. Moreover, LP subjects displayed lower levels of activity and stereotypic behavior than BP and HP subjects. Those identified as non‐stereotypic never displayed stereotypy. In a second experiment, 48 individuals, bred and reared on LP and whose parents were stereotypic, were assigned to either HP (13 males, 12 females) or LP (12 males, 11 females) treatments at 50 days of age for 30 days. Stereotypy was three times less likely to occur in the LP than the HP treatment, and activity was greater in LP‐HP individuals than LP‐LP individuals. In both experiments, LP individuals had the lowest body mass. Striped mice adjusted their behaviors in response to dietary protein levels. Protein deficiency reduced activity and stereotypic behavior and prevalence, possibly related to an energy or neurological deficit.